PENERAPAN AJARAN KAUSALITAS DALAM PASAL 160 KUHP TENTANG TINDAK PIDANA PENGHASUTAN KHUSUSNYA DALAM KASUS KERUSUHAN SAAT DEMONSTRASI (Studi Putusan Pengadilan Negeri Jakarta Pusat No. 160/Pid.Sus/2020/PN.Jkt.Pst) - Muhammad Fikhri Syafarulloh (2021)
This paper discusses the application of the teaching of causality in legal practice in Indonesia. The teachings of causality that have developed in Indonesia include the teaching of conditio sine qua non, the teaching of generalizing, the teaching of individualizing and the teaching of relevance. The teaching of causality must be used to analyze criminal acts with material offenses. The research method used by the author in this research is the normative juridical method. The data processing used in this research is carried out qualitatively by analyzing the provisions of the applicable legislation and decisions that exist or are applied to a particular issue or problem. This writing aims to find answers about the teaching of causality in Indonesia and its application to Article 160 of the Criminal Code. Based on Decision Number 160/Pid.Sus/2020/PN.Jkt.Pst which is used as a case study, the author concludes that judges use probability in deciding cases.